Women, Gender, And Disaster: A Case Study Of Flood Victims In Kota Bharu, Kelantan - Hayrol Aziz, Farah Syazwani; Selamat, Nor Hafizah; Endut, Noraida (2016)
This paper aims to identify the gender issues in flood situation by investigating the experiences of women and men during flood disaster. It is also focusing on factors that contributes to and affects women’s vulnerability during flood. Literature on gender and disasters shows the importance of gender in disaster mitigation to increase women’s resilience to disaster. Therefore, this paper also seeks to understand, whether gender has been adequately addressed in the local disaster management plan and its consequences. Drawing on narrative accounts from three focus group discussions involving 23 respondents, the study investigates the impacts of floods event on women’s lives, livelihoods, and health. The research finding shows that there are still gender gap in flood disaster responses and in the existing disaster management plan. Aids were not equally distributed among victims, with too much emphasized for those who were staying at the flood-evacuation centre while marginalizing those who were staying at relative’s house or other places. Women with small children whose husbands were away have to independently survive, and single mothers were not given enough attention during the emergency times. Therefore, current responses and procedures to flood disaster management model have to be reviewed and gender dimension have to be integrated in order to significantly improve the preparedness and relief program during flood disaster. This study highlights the need of detailed analysis on how disaster or flood affects women and how Disaster Risk Reduction (DRR) planning could be more gender-sensitive.